Self-adapted testing: an overview. (1st January 2002) - Wise, Steven L.; Ponsoda, Vicente; Olea, Julio
A self-adapted test is a computerised test that allows examinees to choose the difficulty levels of the items they have to answer. This paper describes its basic principles and the main research results about its effects on examinees' performance and well-being. Despite some divergent results and compared to computerised adaptive testing, it appears safe to conclude that self-adapted testing decreases anxiety, reduces the correlation between anxiety and proficiency, increases testing time and sometimes increases examinee mean proficiency. Its advantages and liabilities are discussed, along with implications for measurement practice.